Analisis Yuridis terhadap Tindak Pidana Penculikan dalam KUHP Nasional - muhamad rayhan (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the regulation of kidnapping under Articles 450, 451 and 452 of the Indonesian National Criminal Code and examine the normative and practical issues arising from its implementation. The research employs a normative legal method using statutory and conceptual approaches. The findings indicate that the National Criminal Code regulates kidnapping, hostage-taking, and child protection more systematically than the previous Criminal Code. However, several normative issues remain, including the unclear scope of the element of “taking a person,” the overlap between kidnapping and hostagetaking, and the absence of specific provisions addressing technology-based kidnapping methods. The study concludes that a progressive legal interpretation is necessary to ensure effective protection of individual liberty in response to evolving forms of crime.